An Analysis of Students’ Difficulties in Learning English at Senior High School - Willy Valentine (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2026)
English is considered one of the most essential international languages used in communication, education, technology, and global interaction. In Indonesia, English is taught as a foreign language at different educational levels, including senior high school. However, many students still encounter various challenges in learning English effectively. This study aims to analyze students’ difficulties in learning English at senior high school and identify the factors that influence these difficulties. This research applied a descriptive qualitative method involving senior high school students as participants. The data were collected through classroom observation, interviews, and questionnaires to obtain information regarding students’ experiences and challenges in English learning. The findings revealed that students commonly experience difficulties in vocabulary mastery, grammar understanding, pronunciation, speaking confidence, and learning motivation. In addition, environmental factors, teaching strategies, and limited opportunities for practice also influence students’ English learning outcomes. These findings indicate that teachers need to implement interactive teaching strategies and encourage students to participate actively in classroom activities to improve their English skills. Therefore, cooperation between teachers and students is important to overcome learning difficulties and improve English proficiency.